A 15-Year Retrospective on Insertion-Deletion Systems: Progress, Evolution, and Future Directions - Alhazov, Artiom; Ivanov, Sergiu; Verlan, Sergey (Computer science journal of Moldova, 2024)
This paper offers a comprehensive retrospective on the development and results in the field of insertion-deletion systems over the past 15 years, building upon an earlier foundational overview from 2010. We review key theoretical developments, new extensions, and variations that have emerged, examining their impact on the computational power of insertion-deletion systems. This retrospective aims to update the field’s understanding of the model, providing insights into the latest progress and identifying promising directions for future research.